Traditional usage of medicinal plants by Temiar tribes in the State of Kelantan, Peninsular Malaysia - Hassan Zaki, Pakhriazad; Gandaseca, Seca; Mohd Rashidi, Noorhayati; Ismail, Mohd Hasmadi (Universitas Hasanuddin, 2019)
Traditional medicine has deep historical linkages and cultural roots. In a rural community, it is practice based on the ethnological, medical and heritage of the practitioners. Temiar indigenous tribe of Orang Asli in Kelantan, have their traditional way of beliefs and healing practices. This study examines the remedies using medicinal plants and herbs among the tribe members in Kampung Pasik, Kelantan, Malaysia. A structured questionnaire and in-depth interviews were conducted with 250 respondents. A total of 18 species of medicinal plants was recorded preferably used by the tribes. Results indicate that traditional phytoremedies practices play an important role in helping their healthcare system with the help of the tribe healers. Cultivated medicinal plant species represent 94% of the source, whereas 4.4% were found wild in the forest and 1.6% grown around their settlement. This study revealed that five preparations methods such as boiling (27.56%), pounded (27.45%), squeeze (21.60%), drying (14.17%) or concoction of various part of medicinal plants (9.22%). The most applied were by drinking (35.29%), chewing (32.70%) and 19.89% rubbing, poultice (6.40%) and shower ingredients (5.72%).